Rough sets : international joint conference, IJCRS 2017, Olsztyn, Poland, July 3-7, 2017, proceedings /: international joint conference, IJCRS 2017, Olsztyn, Poland, July 3-7, 2017, proceedings. (2017) - Unknown
No abstract available